2015
DOI: 10.1007/s00425-015-2262-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and transcriptome analysis of orange head Chinese cabbage (Brassica rapa L. ssp. pekinensis)

Abstract: The orange head phenotype of Br - or resulted from a large insertion in carotenoid isomerase (BrCRTISO) . Comparative transcriptome analysis revealed that the mutation affected the expression of abundant transcription factor genes. A new orange trait-specific marker was developed for marker-assisted breeding. Orange head leaves are a desirable quality trait for Chinese cabbage. Our previous fine mapping identified BrCRTISO as the Br-or candidate gene for the orange Chinese cabbage mutant. Here, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 52 publications
3
39
1
Order By: Relevance
“…The color of the inner head leaves is usually white, yellow, or orange. The orange color of the inner leaves is a result of the accumulation of prolycopene and other carotenoid pigments [911]. In recent years, the orange head Chinese cabbage varieties have gradually captured the attention of breeders and consumers, since they have an attractive color and higher carotenoids compared with the white and yellow head cabbage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The color of the inner head leaves is usually white, yellow, or orange. The orange color of the inner leaves is a result of the accumulation of prolycopene and other carotenoid pigments [911]. In recent years, the orange head Chinese cabbage varieties have gradually captured the attention of breeders and consumers, since they have an attractive color and higher carotenoids compared with the white and yellow head cabbage.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the BrCRTISO (Bra031539) gene has been identified as the Br-or candidate by several research groups. Many insertions/deletions were identified in this gene [911, 15], resulting in mutant BrCRTISO proteins, which cannot catalyze the conversion from prolycopene to all- trans -lycopene [15]. Furthermore, studies have also shown mutations of the BrCRTISO gene dramatically alter the expressions of many other genes [11, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a 141-bp deletion in the promoter region and 6-bp deletion, as well as 53 SNPs in the first exon, were found in orangetype cultivars. Zhang et al (2015) compared the genomic sequences of two Chinese cabbage materials and found that their differences included an 88-bp deletion in the promoter region, a 501-bp insertion at the 3' end, and two SNPs. The two SNPs cause two amino acid substitutions and a 501-bp insertion, resulting in the addition of 143 amino acids at the end of BrCRTISO.…”
Section: Discussionmentioning
confidence: 99%
“…CRTISO is an important enzyme in carotenoid biosynthesis, catalyzing the prolycopene into lycopene [13]. The genes encoding the CRTISO protein have been isolated in various plant species, including Arabidopsis [3], tomato [4], tobacco [14], and Brassica rapa [15].…”
Section: Introductionmentioning
confidence: 99%